Post-surgical intestinal dysbiosis: use of an innovative mixture (Lactobacillus plantarum LP01, Lactobacillus lactis subspecies cremoris LLC02, Lactobacillus delbrueckii LDD01) - Bonavina, Luigi; Arini, Andrea; Ficano, Leonardo; Iannuzziello, Donato; Pasquale, Luigi; Aragona, Salvo Emanuele; Ciprandi, Giorgio; on digestive disorders, Italian Study Group (Acta Biomedica Atenei Parmensis, 2019)
Abdominal surgery represents a high risk for hospital-acquired infections and complication that may compromise the surgery outcome. Patients with recent abdominal surgery have an intestinal dysbiosis. There is evidence that probiotics may counterbalance the impaired microbiota. Therefore, the current survey evaluated the efficacy and safety of Abincol®, an oral nutraceutical containing a probiotic mixture with Lactobacillus plantarum LP01 (1 billion of living cells), Lactobacillus lactis subspecies cremoris LLC02 (800 millions of living cells), and Lactobacillus delbrueckii LDD01 (200 millions of living cells), in 612 outpatients (344 males and 268 females, mean age 58 years) undergoing digestive surgery. Patients took 1 stick/daily for 8 weeks. Abincol® significantly diminished the presence and the severity of intestinal symptoms and improved stool form. In conclusion, the current survey suggests that Abincol® may be considered an effective and safe therapeutic option in the management of patients undergoing digestivesurgery.